Beauty and Violence in Beauty by Tony Hoagland (PANOPTICON: Journal of English Studies, 2024)
In "Beauty" by American poet Tony Hoagland, the concept of beauty symbolizes women's beauty, which capitalists and the media construct to gain and make a profit. Using the Beauty Myth theory by Naomi Wolf as a guide, this study analyses the beauty standard portrayed in the poem. According to Wolf (1990), beauty is a myth that the media and the beauty industry have created to keep women in a state of constant self-doubt and insecurity. The result is that women are not aware of the many negative influences that they have on women, such as health, deception, excessive fantasy, and, most importantly, the exploitation of women as a result of these many factors. As a result of this negative influence, various criticisms are triggered. The purpose of this article is to examine the social forces that lie behind the existence of this poem from the perspective of a feminist.